A Corpus-based Study of Symbolism in William Golding‟s Lord of the Flies - Faryyad, Farah (International Journal of Psychosocial Rehabilitation, 2020)
Corpus-based literary analysis is getting its momentum nowadays in the hands of researchers around the globe as it offers objective and unbiased results. The present study is a corpus-based analysis of symbolism in William Golding’s novel Lord of the Flies. The main purpose of this study is to compare these given symbols akin to the human nature of modern society. All symbols reflect the theme of the novel and represent the human nature and instinct of civilization and savagery. Both quantitative and qualitative methods are used. Quantitative data was analyzed to check the frequency of the given symbols. For that purpose AntConc 3.5.8 software is used. Ten symbols are selected randomly to analyze the frequency and their use in the novel through concordance tool. Gathered data are categorized according to frequency order, analyzed in descriptive manner for qualitative purposes. The Findings of the study reveal that symbols used by Golding in his novel Lord of the Flies represent the theme of the novel that is the representation of human nature.